The impact of socialization agents on the financial behaviour of university students in Zimbabwe. - Nyota, Hazel (Midlands State University, 2017)
The purpose of this study was to investigate socialization factors influencing financial behaviors among university students in Zimbabwe. In this harsh economy evidenced in Zimbabwe where students’ no longer receive grants and loans, college life seems to be difficult for the university students and the situation requires one to be able to manage their finances well and to be financially literate. Theoretical and empirical literatures were both reviewed on socialization agents so as to make derivations and give the basis for a strong analysis. Studies carried out in other countries were integrated in the empirical literature review and theories such as social learning theory and consumer socialization theory were used to give a theoretical assumption for this study. An explanatory research design was used to measure the strength of relationships between socialization agents and financial behavior. A model was adopted from existing literature and essential adjustments were made to suit the properties of the study. A sample of 368 students was drawn using multi stage cluster sampling technique to allow for different probability sampling methods to be used thus making sampling effective The conclusions of the study indicate that peer influence and media exposure are significant determinants of financial behavior among a large pool of other socialization factors. Through the use of a logistic model, the author provides a model to be used in determining financial behavior. The study recommends that there is need to set up financial literacy programs in schools particularly in primary and secondary schools. Advanced education organizations in Zimbabwe should think about including a personal financial class for students from distinctive academic levels to improve their financial knowledge particularly in the ranges of borrowing and the need to improve the cadetship scheme.